Stilistika dalam 'aurad al-yaum wa laylah' karya Ibnu Arabi - Delami Delami; Ferry Syahputra (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This stylistic research aims to look at the style of language used by Ibn 'Arabi in his work entitled